Detection of Histoplasma Capsulatum in Domestic Chicken Droppings in Olenguruone, Nakuru County - Kemoi Edson Kipyegon; Stanslaus Kiilu Musyoki; Stephen Mwaura Kariuki (European Scientific Journal, ESJ, 2017)
Histoplasmosis is a serious community acquired fungal infection among immunocompetent and immunocompromised individuals. Chicken droppings were evaluated for the presence of Histoplasma capsulatum, by culturing in Blood agar, SABHI and SDA agar at 25°C and 37°C. Exoantigen were used for confirmation. Two Histoplasma capsulatum were isolated in this study. The study found that Chicken droppings harbor Histoplasma species.